2012
DOI: 10.4012/dmj.2011-223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of staining solutions on color of pre-reacted glass-ionomer containing composites

Abstract: This study investigated the color stability of pre-reacted glass-ionomer containing composite restoratives. The materials evaluated included one regular (Beautifil II [BF]), two flowable (Beautifil Flow [F02, F10]) and two recently introduced flowable "plus" (Beautifil Flow Plus [F00, F03]) pre-reacted glass-ionomer containing composite restoratives. Twelve specimens of each material (A3 shade) were fabricated, allowed to set for 24 h at 37°C and randomly divided into 4 groups. After baseline spectrophotometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 18 publications
3
27
0
3
Order By: Relevance
“…So, S-PRG can release and recharge and rerelease fluoride ions. Recent in vitro study [28] in 2012 investigated the color stability of Beautifil II, two flowable (Beautifil Flow [F02, F10]) and two recently introduced flowable "plus" (Beautifil Flow Plus [F00, F03]). The least color change was generally observed with the flowable "plus" pre-reacted glass-ionomer containing composites.…”
Section: Discussionmentioning
confidence: 99%
“…So, S-PRG can release and recharge and rerelease fluoride ions. Recent in vitro study [28] in 2012 investigated the color stability of Beautifil II, two flowable (Beautifil Flow [F02, F10]) and two recently introduced flowable "plus" (Beautifil Flow Plus [F00, F03]). The least color change was generally observed with the flowable "plus" pre-reacted glass-ionomer containing composites.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Compared with resin-based composites, Giomers were shown to have similar mechanical properties in terms of compressive strength, flexural strength, fracture toughness, micro-hardness, and polymerization shrinkage. 23 Studies have been conducted to examine the staining susceptibility of Giomers in food-simulating liquids and limited beverages, 10 but there have been limited studies examining staining susceptibility of nano-ionomers and injectable hybrid Giomers and their performance in comparison to other materials.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Studies have compared and reported on the susceptibility to staining of tooth-colored restorations in different food-simulating liquids or beverages through color or translucency changes. [9][10][11][12][13] Tian & others state that ''most materials are susceptible to staining by 'dark' beverages while distilled water causes no perceptible color change.'' 10 These dark beverages have constantly shown to be coffee and red wine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Cam iyonomer simanların florid salınım özellikleri ile kompozit rezinlerin estetik ve mekanik özelliklerinin kombine edilmesi amacıyla rezin modifiye cam ionomer simanlar ve poliasit modifiye kompozit rezin gibi hibrit restoratif materyaller geliştirilmiştir. 5 Son yıllarda ise yeni grup hibrit kompozit materyaller olan giomerler piyasaya sürülmüş-tür. Bu materyallerde restoratif materyal içerisinde stabil halde cam ionomer üretmek için önceden tepkimeye girmiş cam ionomer teknolojisi (S-PRG) kullanılmaktadır.…”
Section: Introductionunclassified